Market integration of wheat in Pakistan - Jam Ghulam Murtaza Sahito (Justus-Liebig-Universität Gießen, Zentrum für Internationale Entwicklungs- und Umweltforschung (ZEU), 2015)
Understanding market integration in developing countries is an important issue in current research. This study is an attempt to analyze wheat market integration in Pakistan. Previous research on the subject has attempted at analyzing market integration in Pakistan's south and north Punjab regions, mainly relying on co-integration only and not considering advanced dynamic models and transaction costs to analyze the degree of integration. Therefore, this study is a first attempt to analyze the extent of market integration in the whole country using a dynamic model. Monthly wholesale price data of five regional markets from January 1988 to April 2011 are used for this study. Price series were tested for stationarity with the Augmented Dickey Fuller (ADF) test and it was found that all prices are integrated of order one, commonly written as I(1). Co-integration was also identified in all price series pairs using Johansen's co-integration test. The Vector Error Correction Model (VECM) was then applied to the data to analyze the extent of market integration. As a result, it was found that the adjustment to shocks or disequilibrium was higher for the Lahore and Rawalpindi markets as compared to the Hyderabad and Peshawar markets. It might be because of the high consumption, low production and developed infrastructure in these regions. Adjustment coefficients were significant for most of the market pairs. The Threshold Vector Error Correction Model (TVECM) with a band of non-adjustment was applied to incorporate transaction costs, without relying on observations for these costs, which were not available for the study. It was found that linear ECMs or VECMs provide misleading results as compared to TVECMs. Short-run adjustments in the TVECM model provide mixed results depending on regimes as well as markets. Strong adjustments were found in the upper regime, which shows that when price differences are above the second threshold markets tend to adjust significantly.
Keywords: C32; F15; 330; market integration; co-integration; wheat; commodity prices; error correction; thresholds